Pear Deck Media in Online Learning of Writing Explanation Text for Students at Class of XI Senior High School - Lida, Ulfah Mey; Eliya, Ixsir (Universitas Terbuka, 2025)
In this era, the concept of technology-based learning becomes more crucial in education. This study aims to describe the implementation, appropriate selection, and constraints in the implementation of Pear Deck in online learning of explanation text writing for class XI senior high school students. The research approach used in this study is a qualitative descriptive approach. The method of data collection is simak (listening). The data analysis method used is the contextual analysis method. Data interpretation is conducted by connecting the relationships, differences, causes, and implications of the analysis results with the existing theories in the literature review. The results show that Pear Deck implementation in online learning of explanation text writing for the students at class XI senior high school students can be made interactive. The teacher has made the right decision by choosing Pear Deck as a learning medium for explanation text writing. Pear Deck has met the criteria as a decent media used in learning. However, several obstacles are found in the implementation of the media.